Adjuvant immunotherapy in patients with high‐risk muscle‐invasive urothelial carcinoma: The potential impact of informative censoring. Issue 15 (12th May 2022) - Martini, Alberto; Yu, Menggang; Raggi, Daniele; Joshi, Himanshu; Fallara, Giuseppe; Montorsi, Francesco; Necchi, Andrea; Galsky, Matthew D.
Abstract : BACKGROUND: The results of 2 studies exploring adjuvant immune checkpoint inhibition (aCPI) in high‐risk muscle‐invasive urothelial cancer have yielded conflicting results. A trial employing placebo as the control arm demonstrated a significant prolongation in disease‐free survival (DFS) whereas a trial employing observation as the control arm (IMvigor010) demonstrated no prolongation in DFS with CPI. Here, the authors aimed to estimate the aCPI benefit and to model the potential impact of informative censoring on trial results. METHODS: Survival data from 1518 patients was reconstructed from Kaplan‐Meier curves. A network meta‐analysis approach was used to estimate aCPI benefit through the restricted mean disease‐free survival time (RMDFST). To estimate the potential impact of informative censoring on IMvigor010, a simulation was performed. The minimum proportion of informative censoring on the observation arm that could account for the lack of observed improvement in DFS was estimated. Random variability from the time of censoring to progression was modeled using the exponential distribution. RESULTS: Patients receiving aCPI had better DFS: ΔRMDFST at 36 months of 2.2 (95% CI, 0.6‐3.7, P = .006) months relative to observation/placebo. In IMvigor010, in the observation arm, 20.5% of patients were censored due to consent withdrawal, protocol violation and/or noncompliance, or lost to follow‐up versus 8.2% in the treatment arm. On simulation, it was found that the lack of observed improvement in DFS could have resulted from as few as 14% of the censored patients on observation arm not being censored at random (simulated DFS with 14% informative censoring hazard ratio, 0.83; 95% CI, 0.69‐0.99; P = .049). CONCLUSIONS: Phase 3 trials comparing adjuvant therapies to observation are at risk for informative censoring that could potentially impact interpretation of study results.; Abstract : By relying on reconstructed survival data from 2 studies on adjuvant immunotherapy for high‐risk urothelial cancer, the authors show that phase 3 trials comparing adjuvant therapies to observation are at risk for informative censoring that could potentially impact interpretation of study results.